SPIRITUALIZING TECHNOLOGY: OPEN DIALOGUE ACROSS FAITHS IN “LOG IN” ON CLOSE THE DOOR DEDDY CORBUZIER’S YOUTUBE CHANNEL - Suatin, Ricka Milla; Susanti, Dwi (Jurnal Riset Mahasiswa Dakwah dan Komunikasi, 2023)
Podcast content is very diverse, one of which is a da'wah podcast called "Log In" on Close the Door on Deddy Corbuzier's YouTube account. This podcast has been watched by more than 1 million viewers every episode. Seeing this phenomenon, researchers are interested in analyzing the content of da'wah messages in interfaith open discussions on the "Log In" episodes 21 and 22. This research uses a qualitative descriptive method with a content analysis approach. The theory of da'wah messages from Samsul Munir Amin was used in this study and focused on da'wah activities containing three classifications/categories, namely creed, sharia, and morals. The result of this study is that the message of da'wah based on this channel promotes tolerance and respect for followers of other religions and reaches a mutual agreement between the speakers that faith is a matter of the heart. It is supported by speakers who do not confront each other, but engage in intellectual conversation, taking knowledge and positive messages that can be gleaned from one religion and another.